Social Philosophy and the Early Development of Winnipeg's Public Parks - Cavett, Mary; Selwood, H.; Lehr, John (Urban History Review / Revue d'histoire urbaine, 1982)
Winnipeg's earliest parks were developed towards the end of the nineteenth century. Their origins are explained in the wider context of social philosophies prevalent in North America at the time. Although there was a shift in emphasis and an evolutionary trend in their functions, parks were established to serve the interests of real estate promoters and to satisfy the demands of social reformers. They were thus designed both to enhance land values and to improve the quality of life in Winnipeg. By the mid-twenties, the joint efforts of private entrepreneurs and public authorities had created a system of parks and green spaces that catered to the diverse needs and interests of a large proportion of Winnipeg society.